UJI EFEKTIVITAS ANTIINFLAMASI SALEP EKSTRAK DAUN BAYAM MERAH (Amaranthus Tricolor L.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KELINCI JANTAN (Oryctogalus cuniculus) - Desvita Maharani Putri; Na’imatul Retno Faizah; Octaviana Dyah Oentari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Burns are a type of trauma that requires proper handling to speed up the healing process and prevent infection. Red spinach leaves contain active compounds such as flavonoids, tannins, and saponins that have the potential to be anti-inflammatory, antioxidant, and accelerate tissue regeneration. This study aims to test the anti-inflammatory effectiveness of red spinach leaf extract ointment (Amaranthus tricolor L.) on the healing of burns in male rabbits (Oryctogalus cuniculus). In this study using an experimental method, red spinach leaves were extracted by maceration method, burns healing tests used concentration variations in ointment preparations of 5%, 10%, and 15%, positive control using gentamicin ointment and negative control using vaseline flavum. The average result of the burn healing diameter was analyzed with SPSS using the One Way ANOVA test. The results showed that all concentrations of the extract had an effect on wound healing, with a concentration of 15% indicating the best healing effectiveness with an average of 0.88 cm equivalent to a positive control. The ANOVA statistical test obtained a significance value of 0.985 (P>0.05) indicating that H0 was accepted and H1 was rejected, which shows that the data did not show significant differences between groups, but clinically it was seen that wound healing was faster at higher concentrations of extracts. This study supports the potential use of red spinach leaf extract ointment as an alternative to treating mild to moderate burns.